Multiplicidade Transcendente: imaginário e arquétipos na lírica feminina - Capitani, Dhandara (2019)
The Imaginary is not a finished and unchanging set of images that already exists on certain themes, but comprehends the potentialities of human creation, including the possibilities of diachronic changes and transpositions. By a mimetic process, literature represents the world – hence, understanding and analyzing literature means understanding and analyzing the world and humanity, represented. Through the study of images and symbols, especially when crystallized by the aesthetic elaboration of poetry, "the archetype diversifies and unifies the messages of the unconscious Self" (DURAND, 1995, p. 37). Considering the question of feminine literature, for long women were muses and not writers, which meant their representation came from an external perspective. Thus, this research is based on the premise that when women write themselves about their own context and experiences, they recreate and re-elaborate elements of a feminine imaginary, creating a legacy of unique value for the understanding of women. In this context, the objective of this research was to analyze three different archetypal sets – the Wild Woman, the Mother and the Elder. In addition to these, the poets demonstrate that in most of the poems whose theme is the feminine, the representation transgresses the archetypal limits. Similarly, when they write metapoems with a female enunciating voice, the representations reach a level of multiplicity that transcends limits. The methodology chosen was a bibliographical review, analyzing the poetic work of four contemporary poets, Adélia Prado, Ana Cristina Cesar, Alejandra Pizarnik, and Maya Angelou, selecting poems whose subject was the feminine and women, or that had a marked female enunciating voice. From this selection, about ten poems were analyzed for each archetypal matrix. Essentially, the images and ideas connected to the Wild Woman archetype point to a regaining of female wisdom in its most primitive form – taking the word as we understand the archetypes themselves, that is, primordial. The Maternal archetype is complex and involves the mysteries of life and death, for in the feminine as the power of creation and, as consequence, the responsibility of creating into an existence that inevitably end in death. Under the Archetype of the Elder, the theme of death as part of life becomes even more pronounced. When searching for themselves, for the essence of words and for the essence of the poetic word, poets re-elaborate images on the creating power, in a poetic process that I proposed to name Transcendental Multiplicity. For the studies on Poetic Creation, Archetypes and Imaginary, the theories of authors such as Gaston Bachelard (1994, 1997, 2018), Gilbert Durand (1995, 1996, 2001, 2014), Clarissa Pinkola Estés (2014), Carl Gustav Jung (2000a , 2000a, 2007, 2017), Octavio Paz (1981, 2006), and Anchyses Jobim Lopes (1996) were essential. As references on feminism and feminine writing, the studies of Simone de Beauvoir (1990, 2016a, 2016b), Donna Haraway (1995), Ana Cristina Cesar (1999), Heloísa Buarque de Hollanda (1982, 1994, 2011), and Hélène Cixous (1995) were fundamental.